2016
DOI: 10.1016/j.irfa.2015.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in hedge funds' performance attribution: Performance persistence and fundamental factors

Abstract: We survey articles on hedge funds' performance persistence and fundamental factors from the mid-1990s to the present. For performance persistence, we present some pioneering studies that contradict previous findings that hedge funds' performance is a short term matter. We discuss recent innovative studies that examine the size, age, performance fees and other factors to give a 360° view of hedge funds' performance attribution. Small funds, younger funds and funds with high performance fees all outperform the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Interesting findings concerning the phenomenon under study were presented by Stafylas et al (2016), who proved that hedge funds can maintain their performance in the short and long term, and also pointed out that as regards age and size, small and young funds were more likely to maintain positive rates of return. Sun et al (2018) provided evidence that fund managers are unlikely to ensure performance persistence and that hedge fund performance is persistent following a period of underperformance.…”
Section: Literature Reviewmentioning
confidence: 98%
“…Interesting findings concerning the phenomenon under study were presented by Stafylas et al (2016), who proved that hedge funds can maintain their performance in the short and long term, and also pointed out that as regards age and size, small and young funds were more likely to maintain positive rates of return. Sun et al (2018) provided evidence that fund managers are unlikely to ensure performance persistence and that hedge fund performance is persistent following a period of underperformance.…”
Section: Literature Reviewmentioning
confidence: 98%
“…Linear multi factor models are used to measure hedge fund performance in several studies, like Schneeweis and Spurgin (1999), Capocci (2002) or Jordao and De Moura (2011). Despite the application to hedge fund performance, the linear models are more suitable to evaluate traditional funds because they fail to capture hedge fund characteristics like time variation (Stafylas et al 2017). Furthermore, Slavutskaya (2013) concluded that linear factor models are not suitable for hedge funds as they lead to over-parameterisation, because many hedge funds have a life of three years.…”
Section: Performance Measurement Modelsmentioning
confidence: 99%
“…Although non-linear multifactor models can explain hedge fund returns in a more detailed way and account for special characteristics of hedge funds, they might not be best for investors' performance evaluation. This is mainly due to the fact that exposures are not static and, therefore, need to be adjusted and that the models and factors are complicated to replicate (Stafylas et al 2017).…”
Section: Performance Measurement Modelsmentioning
confidence: 99%
“…In addition, according to their results, the performance of the various classes of mutual funds seemed to be invariant relative to market conditions. Stafylas et al [17] pointed out several factors that influence hedge fund performance, namely size, age and fees. Hwang et al [18] concluded that systemic risk is a prevailing cause of cross-sectional deviations in hedge fund returns.…”
Section: Literature Reviewmentioning
confidence: 99%